A "double fistula" with Mycobacterium avium complex lung disease. Issue 8 (5th July 2021) - El Haj Chehade, Ahel; Raphael, Ibrahim; Brown, Brent; Abdo, Tony
Key message: We present a patient with a history of cavitary mycobacterial lung infection and chronic obstructive pulmonary disease (COPD) who developed two connected fistulas post thoracentesis, an alveolo‐pleural and a pleuro‐cutaneous fistula, leading to continuous air leak from a stoma on his back. Abstract : We present a patient with a history of cavitary mycobacterial lung infection and chronic obstructive pulmonary disease (COPD) who developed two connected fistulas post thoracentesis, an alveolo‐pleural and a pleuro‐cutaneous fistula, leading to continuous air leak from a stoma on his back.